Postgraduate supervision support in Open Distance and E-learning: Supervisors’ and key stakeholders’ views - Gumbo, M. T.; Gasa, V. (South African Journal of Higher Education, 2023)
This descriptive case study explores the support that supervisors in the College of Education (CEDU) at the University of South Africa (UNISA) give to Ethiopian doctoral students. It is important to inquire into supervisors’ views about the support that they give to students as part of their supervision especially in the open distance and e-learning (ODeL) higher education context. Twelve supervisors who are or have supervised Ethiopian doctoral students were selected by convenience sampling and interviewed individually to gather their views about the support they give (or have given) to their students. Supervisors’ views were augmented by other key stakeholders’ views to deepen the understanding of support. The findings reveal that supervisors, though faced with unique challenges, made efforts to support students emotionally, academically, and by being the extended hand of UNISA when students could not access certain services or resources. Doctoral students who are faced with contextual challenges can succeed if they are given proper support which is motivated by mutual respect between the supervisor and student. The study can also benefit supervisors in African universities to reflect on the support that they give to their students, especially in the situations that are posed by the students’ circumstances.